The Bub1–Plk1 kinase complex promotes spindle checkpoint signalling through Cdc20 phosphorylation - Luying Jia (Nature Portfolio, 2016)
The mitotic checkpoint complex (MCC) inhibits the anaphase-promoting complex (APC/C) bound to Cdc20 in response to spindle defects. Here, the authors show that Bub1-Plk1-mediated phosphorylation of Cdc20 constitutes a parallel, non-redundant APC/C-inhibitory mechanism in addition to MCC activity.